The effectiveness of digital nutrition education interventions on behavioral changes in fast food consumption - Indriati Kusumaningsih; Patemah Patemah; Ni Ketut Wiradnyani; Aliah Bagus Purwakania Hasan; Andi Maulana Kamri (AcTion: Aceh Nutrition Journal, 2025)
The consumption of fast food has increased significantly and is associated with obesity and other chronic diseases. Digital nutrition education has been proposed as a solution to promote healthy eating behaviors. This randomized controlled trial was conducted in Jakarta and Bandung, Indonesia, in 2024 and involved 200 participants aged 18–50 years old. The experimental group (n=100) received digital nutrition education through a mobile application, whereas the control group (n=100) received no intervention. Data on fast-food consumption frequency, nutritional knowledge, and attitudes were collected using validated questionnaires before and after the 6-week intervention. Fast food consumption in the experimental group decreased significantly by 53% (from 6.5 to 3 times/week) compared with a 12% reduction in the control group. Nutritional knowledge improved from 40% to 75%, and 80% of the participants reported improved eating habits. Higher engagement with interactive app features led to a 30% increase in healthy food consumption. Digital nutrition education interventions effectively reduce fast food consumption and improve nutritional knowledge and attitudes. These findings support the integration of digital tools into public health strategies.